Decolonizando a África: o uso da tecnologia educacional para uma educação antirracista no ensino de História - CARDIN, Hortência Keize Araújo (Universidade Federal do Pará, 2023)
The Teaching of History was directly affected by the sanction of Law nº 10.639 / 2003 which makes the theme of “Afro-Brazilian History and Culture” mandatory in the official curriculum of the Teaching Network, the Teaching of History along its trajectory was guided by a curriculum based on a Eurocentric world view, which resulted in the reproduction of stereotypes about the African continent and its descendants, thus, the objective of this research is to show the importance of teaching history from a decolonial perspective and that can contribute significantly to the formation of an anti-racist historical conscience. The research was carried out with 6th grade students and based on the data obtained, new practices and approaches were proposed for the Teaching of African History, which culminated in the final product of this dissertation in the context of the Postgraduate Program in Teaching History ( PROFHISTÓRIA) with the production of an Educational Technology, materialized through a board game called "Decolonizing Ancient Africa" that presents the diversity of Africa and Afro-Brazilian culture, thus contributing for the educational system to become more and more more focused on the education of ethnic-racial relations from an anti-racist education.